Pengaruh Model Project Based Learning terhadap Aspek Perkembangan Nilai Agama dan Moral Anak Usia Dini - Andepi Daryana; Nida Nur Hidayah (Jurnal El-Audi, 2025)
This research is motivated by the low development of religious and moral values ??in children at the Gotong Royong Playgroup. This low development encourages the need for innovation in learning models. One of the efforts used is the implementation of the project-based learning (PjBL) model. This model is believed to be able to increase children's active involvement, encourage social interaction, and develop aspects of religious and moral values ??comprehensively. In addition, the use of PjBL provides a variety of learning models that are more interesting and meaningful. The purpose of this study is to determine the effect of the implementation of PjBL on the development of religious and moral values ????of early childhood and to test its level of significance. This study uses a quantitative approach with an experimental method. Data were collected through observation, interviews, questionnaires, and documentation to obtain a comprehensive picture. The results show that the implementation of PjBL in the Gotong Royong Playgroup is quite good, with the average development of children's religious and moral values ????in the beginning to develop category. Regression analysis produces the equation Y = 4.124 - 1.028 X, and the significance test shows a Sig. 0.001 < 0.05. This means that there is a significant influence of the implementation of PjBL on the development of religious and moral values ??in early childhood. Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected.